Pengaruh Inovasi Produk dan Persepsi Harga terhadap Keputusan Pembelian : Survei pada Konsumen UMKM Habib Collection Kabupaten Tasikmalaya - Leli Nispi Fauzi; Ari Arisman; Depy Muhamad Pauzy (CV. Ulil Albab Corp, 2022)
This study aims to determine the effect of procduct innovation and price perception on purchasing decisions on Habib Collection UMKM consumers in Tasikmalaya Regency. The method used is quantitative research with survey method and causality approach. With a research sample of 97 Consumers of UMKM Habib Collection in Tasikmalaya Regency. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 25.0. The results showed that simultaneously product innovation and price perception had a significant effect on purchasing decisions for Habib Collection products, Tasikmalaya Regency. Partially, product innovation has no significant effect on purchasing decisions for Habib Collection Regency products.